2018
DOI: 10.1016/j.chom.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphatidylinositol 3-Kinase Effector Alters Phagosomal Maturation to Promote Intracellular Growth of Francisella

Abstract: Many pathogenic intracellular bacteria manipulate the host phago-endosomal system to establish and maintain a permissive niche. The fate and identity of these intracellular compartments is controlled by phosphoinositide lipids. By mechanisms that have remained undefined, a Francisella pathogenicity island-encoded secretion system allows phagosomal escape and replication of bacteria within host cell cytoplasm. Here we report the discovery that a substrate of this system, outside pathogenicity island A (OpiA), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 70 publications
4
68
0
Order By: Relevance
“…Interestingly, the latter study also identified putative effector proteins encoded outside of the FPI for F. novicida, including OpiA. In a follow up study, this protein was shown to possess phosphatidylinositol 3-kinase-activity, alter phagosomal maturation, and, thereby, promote intracellular growth of F. novicida (Ledvina et al, 2018).…”
Section: Putative T6ss Effectorsmentioning
confidence: 88%
“…Interestingly, the latter study also identified putative effector proteins encoded outside of the FPI for F. novicida, including OpiA. In a follow up study, this protein was shown to possess phosphatidylinositol 3-kinase-activity, alter phagosomal maturation, and, thereby, promote intracellular growth of F. novicida (Ledvina et al, 2018).…”
Section: Putative T6ss Effectorsmentioning
confidence: 88%
“…As part of an effort to determine the function of a Francisella effector, OpiA, LegA5 was found to possess PI 3-kinase activity. LegA5 contains two motifs, DXHXXN and IDH, separated by 14 amino acids that are characteristic of the catalytic and activation loops of PI 3-kinases (and PI 4-kinases) [52]. PI(3)P has been shown to accumulate on the LCV early during infection in a manner independent of effector protein translocation [12].…”
Section: Pneumophila Converts the Phagosome To A Pi(4)p-rich Vacuomentioning
confidence: 99%
“…By promoting or preventing cytoskeleton re-arrangements through the action of specific effectors that target actin or tubulin, the T6SSs of Vibrio cholerae, Aeromonas hydrophila, and Pseudomonas aeruginosa disable phagocytic cells or stimulate internalization into non-phagocytic cells (21,22,(24)(25)(26). Other T6SSs have been demonstrated to manipulate host cells, although the molecular determinants are not yet entirely understood (27)(28)(29)(30). However, T6SS gene clusters are widespread in Gram-negative bacterial genomes, and not restricted to pathogens (10).…”
Section: Type VI Secretion System Effectorsmentioning
confidence: 99%